Influence of Xylopia Aethiopica Fruits on Some Hematological and Biochemical Profile - Nnodim Johnkennedy1*, Emejulu Adamma2, Amaechi Austin3 and NwosuNjoku Emmanuel Chukwunyere4 (Al Ameen Medical College, 2011)
The present study was carried out to evaluate the effect of some hematological and biochemical profile on Wister albino rats treated with different concentration of Xylopia aethiopica fruit extract for 14days. 200mg/body weight, 150mg/body weight and 100mg/body weight of the extract were given to different groups while the control group received distilled water. The result showed the increase in haematological parameters was dose dependent. This implies that haemoglobin concentration, packed cell volume, red blood cell count and platelet were significantly increased when compared with the control (P<0.05). While serum cholesterol, triglyceride and LDL were significantly decreased when compared with the control (P<0.05). Also, serum potassium and sodium were increased when compared with the control(P<0.05). Hence, Xylopia aesthiopica are used in folk medicine for arresting bleeding among women that put to bed as well as treating cardiovascular and diabetic diseases. Also, this plant may be a good factor in the maintenance of electrolyte balance.